Using real polar terrestrial gravimetry data to overcome the polar gap problem of GOCE - the gravity field model IGGT_R1C - Lu, Biao; Förste, Christoph; Barthelmes, Franz; Petrovic, Svetozar; Flechtner, Frank; Luo, Zhicai; Zhong, Bo; Zhou, Hao; Wang, Xiaolong; Wu, Tangting (GFZ Data Services, 2018)
Abstract With the successful completion of ESA's PolarGAP campaign, terrestrial gravimetry data (gravity anomalies) are now available for both polar regions. Therefore, it is now possible to overcome the GOCE polar gap by using real gravimetry data instead of some regularization methods. But terrestrial gravimetry data needs to become filtered to remove the high-frequency gravity information beyond spher. harm. degree e.g. 240 to avoid disturbing spectral leakage in the satellite-only gravity field models. For the gravity anomalies from the Arctic, we use existing global gravity field models (e.g., EGM2008) for this filtering. But for the gravity anomalies from Antarctica, we use local gravity field models based on a point mass modeling method to remove the high-frequency gravity information. After that, the boundary-value condition from Molodensky's theory is used to build the observation equations for the gravity anomalies. Finally, variance component estimation is applied to combine the normal equations from the gravity anomalies, from the GOCE GGs (e.g., IGGT_R1), from GRACE (e.g., ITSG-Grace2014s) and for Kaula's rule of thumb (higher degree/order parts) to build a global gravity field model IGGT_R1C without disturbing impact of the GOCE polar gap. This new model has been developed by German Research Centre for Geosciences (GFZ), Technical University of Berlin (TUB), Wuhan University (WHU) and Huazhong University of Science and Technology (HUST).Parametersstatic model modelname IGGT_R1Cproduct_type gravity_fieldearth_gravity_constant 0.3986004415E+15radius 0.6378136460E+07max_degree 240norm fully_normalizedtide_system tide_freeerrors formal